2019
DOI: 10.1055/s-0039-3401996
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stage Hybrid Arch Repair for Patients with Shaggy Aorta

Abstract: Operating on extended arch aneurysms that contain severe atherosclerotic plaques is difficult. In such cases, the incidence of intraoperative multiple embolization is very high. We applied single-stage hybrid arch repair, which involved ascending aorta replacement and debranching of arch vessels, consecutively with endovascular repair for two patients. This technique was developed to prevent embolization of atherosclerotic plaques during cardiopulmonary bypass, and abrasion of the plaques during thoracic endov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…14,18,21,51,71 Singlestage hybrid arch repair, which involved ascending aorta replacement and debranching of arch vessels, consecutively with endovascular repair could represent a valid option in patients with SA. 72 In ascending aortic aneurysm, complicated with atherosclerotic lesions of the descending aorta, a hybrid approach using frozen elephant trunk technique could be a valid treatment to reduce the embolism risk. 54 Uchida et al 28 reported a modified arch-first technique in a patient with arch aneurysm complicated by SA, involving arch replacement with a beating heart after reconstruction of supra-aortic vessels while maintaining normal blood pressure.…”
Section: Resultsmentioning
confidence: 99%
“…14,18,21,51,71 Singlestage hybrid arch repair, which involved ascending aorta replacement and debranching of arch vessels, consecutively with endovascular repair could represent a valid option in patients with SA. 72 In ascending aortic aneurysm, complicated with atherosclerotic lesions of the descending aorta, a hybrid approach using frozen elephant trunk technique could be a valid treatment to reduce the embolism risk. 54 Uchida et al 28 reported a modified arch-first technique in a patient with arch aneurysm complicated by SA, involving arch replacement with a beating heart after reconstruction of supra-aortic vessels while maintaining normal blood pressure.…”
Section: Resultsmentioning
confidence: 99%